2013
DOI: 10.1016/j.niox.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of DAF-FM activation by NO: Toward calibration of a NO-sensitive fluorescent dye

Abstract: Nitric oxide (NO) research in biomedicine has been hampered by the absence of a method that will allow quantitative measurement of NO in biological tissues with high sensitivity and selectivity, and with adequate spatial and temporal resolution. 4-amino-5-methylamino-2′,7′-difluorofluorescein (DAF-FM) is a NO sensitive fluorescence probe that has been used widely for qualitative assessment of cellular NO production. However, calibration of the fluorescent signal and quantification of NO concentration in cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…(5)), DAF-2 must compete with the numerous cellular targets for these species. To test this expectation, we treated cells with different concentrations of DAF-2-DA (5, 10, and 20 mM), a procedure that has been shown to increase DAF-2 concentration intracellularly [10,48,49]. As expected, the rate of DAFT formation was greater for higher DAF-2-DA loading concentrations, and the effect was evident at 2 and 10 mM sper/NO (data not shown).…”
Section: Rate Of Intracellular Daft Formation As a Function Of Daf-2-mentioning
confidence: 80%
“…(5)), DAF-2 must compete with the numerous cellular targets for these species. To test this expectation, we treated cells with different concentrations of DAF-2-DA (5, 10, and 20 mM), a procedure that has been shown to increase DAF-2 concentration intracellularly [10,48,49]. As expected, the rate of DAFT formation was greater for higher DAF-2-DA loading concentrations, and the effect was evident at 2 and 10 mM sper/NO (data not shown).…”
Section: Rate Of Intracellular Daft Formation As a Function Of Daf-2-mentioning
confidence: 80%
“…The fluorescein derivatives DAF-FM and DAF-2 were widely used to detect the presence of nitric oxide (for oxygen containing samples or N 2 O 3 (in the absence of oxygen) (27,61,(77)(78)(79)(80)(81)(82). A recent study (77) showed that in the presence of dioxygen, NO 2 rather than N 2 O 3 was likely to be the primary agent altering the DAF resulting in the enhanced fluorescence. In this study, the use of anaerobic conditions essentially eliminates that mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Choroidal capillary endothelial cells from the eyes of Thbs1 -/-mice had elevated phosphorylation of eNOS relative to WT cells, and intracellular NO in the null cells assessed using 4-amino-5-methylamino-2,7-difluorofluorescein (DAF) was sixfold higher than in WT cells. One should bear in mind that DAF is primarily detecting an oxidative product of NO rather than NO itself (176).…”
Section: Fig 2 Overview Of Matricellular Protein Functions In Cellumentioning
confidence: 99%